Studies toward Oxyacetamide-Linked RNA Analogues: Synthesis and Conformation of a Modified Dinucleoside - Jabgunde, Amit M.; Yeole, Sachin D.; Sanap, Shrihari P.; Gadre, Shridhar R.; Dhavale, Dilip D. (Synthesis, 2012)
A new oxyacetamide-modified dinucleoside with 5′-(S) chirality, a hydrophobic 5′-C-(2-methoxyethyl) group, and a 2′-O-methyl group was synthesized from d-glucose. This dinucleoside showed a helical structure based on CD and NMR spectroscopy. The sugar puckering at the 5′ and 3′ ends were found to be ‘S’- and ‘N’-types, respectively. These results were substantiated by ab initio density functional theory.
Keywords: modified dinucleoside; circular dichroism; oxyacetamide backbone; antisense agents; carbohydrates